Hasil Padi dari Empat Kelas Benih Yang Berbeda - Mulsanti, Indria W.; Wahyuni, Sri; Sembiring, Hasil (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
There is conflicting informations regarding the advantages of planting of stock seed (SS) over Extension Seed (ES) classes. An experiment to study the effect of different seedclasses on grain yield and yield components of five rice varieties was carried out at two locations i.e. Sukamandi and Muara Field Station during the wet and dry season of 2009. The treatment consisted of five rice varieties, namely: Ciherang, Mekongga, IR64, Cigeulis and Situ Bagendit, and their respective seed classes: namely breeder seed, foundation seed, stock seed and extension seed. The experiment was arranged in a split plot design with three replications, where rice varieties were as main plots and seed classes as sub plots. Variables to be evaluated consisted of: quality of seed before sowing, plant growth, yield components and grain yield. Performance of the observed variable of each rice variety derived from four different seed-classes in each location and planting season were not significantly different. Differences of seed classes only affected the percentage of seed purity. There was no significant difference on the grain yield and the seed yield obtained from different seed classes of each variety. These results disprove the belief that the higher seed class the higher productivity, which was found to be a wrong perception. Seed certification is designed to maintain the genetic purity of variety and not to increase the productivity.